Rutting Performance of Semi-Rigid Base Pavement in RIOHTrack and Laboratory Evaluation - Li, Sheng; Fan, Mengmeng; Xu, Lukai; Tian, Wendi; Yu, Huanan; Xu, Ke (Frontiers in Materials, 2021)
Through simple performance dynamic modulus test (SPT), standard rutting test, Hamburg rutting test, French rutting test and asphalt pavement analyzer (APA) rutting test, the rutting resistance of asphalt mixtures in the middle and lower courses of three semi-rigid base asphalt pavement of Beijing full-scale test track road in China was evaluated. The test results show that the rutting resistance of asphalt mixtures of middle and lower course can be greatly improved by using low-grade asphalt, especially 30# asphalt. The rutting resistance of SBS modified asphalt mixtures is also better. The SPT dynamic modulus test can indirectly characterize the rutting performance of asphalt mixture. The rutting test results of laser road detection vehicle and 3m ruler show that the asphalt grade has a significant impact on the rutting performance of semi-rigid base asphalt pavement. Compared with 70# asphalt used in the middle and lower course, the rutting resistance of pavement structure can be improved by more than 20%. The APA rutting test results have a close approximation with the full-scale test track results. It is an optimal test method for evaluating the rutting performance of semi-rigid base asphalt pavement. The research results can provide a theoretical basis and reference for the rational design and rutting evaluation of semi-rigid base asphalt pavement.